2017
DOI: 10.1016/j.prro.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated Dynamic WaveArc therapy reduces the dose to the hippocampus in patients with pituitary adenomas and craniopharyngiomas

Abstract: Although VMDWAT increased brain V5 and the treatment time compared with coVMAT, it significantly reduced the dose to the hippocampus and brain V10 to V50 and improved target conformity and homogeneity. VMDWAT could be a promising treatment technique for pituitary adenomas and craniopharyngiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…8 The Vero4DRT has been applied to various clinical scenarios including lung, liver, pancreas, breast, prostate, bone, and brain. [9][10][11][12][13] Monte Carlo modeling is a useful option for providing secondary dose calculation verification and has the added benefit of providing "gold standard" dose calculations in inhomogeneous materials. 14…”
Section: Introductionmentioning
confidence: 99%
“…8 The Vero4DRT has been applied to various clinical scenarios including lung, liver, pancreas, breast, prostate, bone, and brain. [9][10][11][12][13] Monte Carlo modeling is a useful option for providing secondary dose calculation verification and has the added benefit of providing "gold standard" dose calculations in inhomogeneous materials. 14…”
Section: Introductionmentioning
confidence: 99%
“…Since then, DWA has been added to noncoplanar VMAT techniques to achieve better exibility in dose shaping while keeping dosimetrically effective delivery. DWA has been reported to have dosimetric advantages over coplanar VMAT (co-VMAT) in tumors located in the midline of the body, such as skull base tumors and prostate cancers [11,12]. A study on the application of DWA in cases of LAPC using preclinical versions of the treatment planning system (TPS) concluded that it has comparable dosimetric distributions to co-VMAT (13).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, DWA has been added to noncoplanar VMAT techniques to achieve better exibility in dose shaping while keeping dosimetrically effective delivery. DWA has been reported to have dosimetric advantages over coplanar VMAT (co-VMAT) in tumors located in the midline of the body, such as skull base tumors and prostate cancers [17,18]. A study on the application of DWA in cases of LAPC using preclinical versions of the treatment planning system (TPS) concluded that it has comparable dosimetric distributions to co-VMAT [19].…”
Section: Introductionmentioning
confidence: 99%